Respuesta :

Answer:

q(r(4)) = -61

Step-by-step explanation:

q(x) = -2x +1

r(x) = 2x^2 - 1

q(r(4))

First find r(4)

f(4) = 2 (4)^2 -1

      = 2 *16 -1

      = 32-1

     = 31

Then put this value in for x in q(x)

q(r(4)) = q(31) = -2(31)+1

                     = -62+1

                     = -61

Answer:

The value of q( r(4) ) = -61

Step-by-step explanation:

It is given that,

q(x) = - 2x +1

r(x) = 2x^2 - 1

To find the value of q(r(4))

r(x) = 2x^2 - 1

r(4) = 2( 4^2) - 1  [Substitute 4 instead of x]

 = 2(16) - 1

 = 32 - 1 = 31

q( x ) = -2x +1

q( r(4) ) = q(31)        [Substitute 31 instead of x)

 =  (-2*31) +1

 = -62 + 1 = -61

Therefore the  value of q(r(4)) = -61

ACCESS MORE